Atlas of blood cell differentiation interactive reference on CD-ROM - Cillessen, F.; Van der Meer, W. (Amsterdam : Elsevier Science, 1998)
This CD-ROM assist in the evaluation of peripheral blood smears, in the maintenance and increase of expertise, and in the instruction of basal blood cell morphology
System requirements: 386-PC with 8MB RAM, 1 MB VGA graphics adapter and device driver adjusted to at least 65K colors, VGA color monitor, double speed CD-ROM player, 3MB of free disk space, mouse or equivalent pointing device
Keywords: Blood Cells -- atlases